Quality of 'Fuji' apples affected by nitrogen and potassium fertilization in two soil types Qualidade de maçãs 'Fuji' influenciada pela adubação nitrogenada e potássica em dois tipos de solo - de Souza F. (2013)
Fuji' apple trees grown on Inceptisol and Entisol were annually fertilized with doses of N and K2O (0, 50, 100, and 200 kg ha-1, for both) along nine growing seasons. Changes of fruit maturity and quality at harvest and after cold storage in response to N and K2O fertilization were not the same for the two soil types. The increment of N rate applied increased the N content and reduced the starch content and peel red color of the fruit in both soils, regardless of K2O rate. On the Entisol, the increment of N rate increased the fresh mass and reduced the flesh firmness of the fruit, regardless of K2O rate, while in the Inceptisol this response was not consistent. Fruit titratable acidity (TA) reduced with the increment of N rate in both soils, especially at low rates of K2O. For the orchard on Inceptisol, the K and starch contents, TA, fresh mass, and peel red color increased, while the flesh firmness reduced consistently and independently of N rate, with the increment of K2O rate, but not for the orchard on the Entisol. The effects of N and K2O rates on flesh firmness and TA of the fruit were more evident after cold storage than at harvest.